Design and testing of prefabricated steel frame with an innovative re-centering energy dissipative brace. (15th December 2019) - Zhang, Ailin; Ye, Quanxi
Highlights: The energy dissipation of the RCED-BF was almost determined by the RCED brace. The stiffness of the RCED-BF was dominated by the RCED brace. With the increase of the maximum structural response, the energy dissipation coefficient would decrease continuously. A value of 1.2 could be taken as the re-centering resistance coefficient. Abstract: Traditional steel frames will experience large residual drifts under strong earthquakes. An innovative re-centering energy dissipative (RCED) brace was developed, which was able to pull steel frames back to their initial positions after an earthquake and dissipate energy by a friction damper device. In order to study the re-centering and energy dissipation capacities of RCED braced frame (RCED-BF), a prefabricated steel frame (PSF) and three RCED-BFs were designed and tested. The results show that the RCED-BF almost dissipated all the energy by the RCED brace. The diameter of high-strength bolts affected the energy dissipation capacity of RCED-BF significantly, while that of tendons did not. The maximum theoretical value of the energy dissipation coefficient of RCED-BF was 4, which decreased continuously with the increase of the maximum lateral deformation of RCED-BF. The stiffness of the PSF was fairly small and therefore the stiffness of RCED-BF was dominated by RCED brace. A value of 1.2 could be taken as the re-centering resistance coefficient of the RCED-BF.